Low-density lipoprotein cholesterol target attainment in patients with stable or acute coronary heart disease in the Asia-Pacific region: results from the Dyslipidemia International Study II. (29th August 2020) - Poh, Kian-Keong; Ambegaonkar, Baishali; Baxter, Carl A; Brudi, Philippe; Buddhari, Wacin; Chiang, Fu-Tien; Horack, Martin; Jang, Yangsoo; Johnson, Brett; Lautsch, Dominik; Sawhney, JPS; Vyas, Ami; et al.
Abstract: Background: As mortality due to cardiovascular disease increases throughout the world, accurate data on risk factors such as hyperlipidemia are required. This is lacking in the Asia-Pacific region. Design: The observational Dyslipidemia International Study (DYSIS) II was established to quantify the extent of hyperlipidemia in adults with acute and stable coronary heart disease globally. Methods: Patients with stable coronary heart disease or hospitalised with an acute coronary syndrome were enrolled across nine Asia-Pacific countries from July 2013 to October 2014. Lipid-lowering therapy and low-density lipoprotein cholesterol target attainment (<70 mg/dL) were assessed. The acute coronary syndrome cohort was followed up 4 months post-discharge. Results: Of the 4592 patients enrolled, 2794 had stable coronary heart disease and 1798 were admitted with an acute coronary syndrome. In the coronary heart disease cohort, the mean low-density lipoprotein cholesterol level was 86.9 mg/dL, with 91.7% using lipid-lowering therapy and 31% achieving low-density lipoprotein cholesterol of less than 70 mg/dL. In the acute coronary syndrome cohort at admission, the corresponding values were 103.2 mg/dL, 63.4% and 23.0%, respectively. Target attainment was significantly higher in lipid-lowering therapy-treated than non-treated patients in each cohort (32.6% vs. 12.9% and 31.1% vs. 9.0%, respectively). Mean atorvastatin-equivalent dosages were low (20 ± 15 and 22 ± 18 mg/day, respectively), with little use of non-statin adjuvants (13.0% and 6.8%, respectively). Low-density lipoprotein cholesterol target attainment had improved by follow-up for the acute coronary syndrome patients, but remained low (41.7%). Conclusions: Many patients in Asia at very high risk of recurrent cardiovascular events had a low-density lipoprotein cholesterol level above the recommended target. Although lipid-lowering therapy was common, it was not used to its full potential.